THE INDUSTRIAL ENGINEER AS ENTERPRISE DESIGNER - Rottier, Johan (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: A method is proposed by which the suitabilityof development capabilitiescan be evaluated for Enterprise design. The method is based on a model for development and models for various aspects of Enterprises. The evaluation approach is based on correlating the methodology, tools and techniques and knowledge base ofthe capabilitywith that required for the engineering of Enterprises. AFRIKAANSE OPSOMMING:'n Metode word voorgestel om ontwikkelingsvermoe-ns se geskiktheid vir die ontwerp van ondememings te evalueer. Die metode is enersyds gebaseer op 'n model vir ontwikkeling en andersyds op modelle wat die ontwikkelingsvereistes tov Ondememingstoelig. Die evaluasie geskied deur die metodologie, kennisbasisen ontwikkelings hulpmiddelsvan die vermoe te vergelyk met die vereistes wat die ontwikkeling van 'n Ondememing stel.